Reading the Old Testament An Introduction - Boadt, Lawrence (New York Paulist Press, 1984)
Daily life in Ancient Israel - Great prophets including, Hosea, Amos, Isaiah - People and lands of the Old Testament.
Keywords: Bible. -- Old Testament -- Introductions. Bible. -- A.T. -- Introductions. Bible. -- Old Testament